BMS671: Ethical & Legal Issues in Biotechnology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2016)
In this syllabus, the topics include moral and ethical issues of biotechnology, disadvantages and disadvantages of using biotechnology, legal issues pertaining to biotechnology, issues of concern in biotechnology and scope of work of a plant biotechnologist. Students are taught on a self learning basis using a combination of distance learning, self study, group interactions and tutorials.